An integrated connectivity risk ranking for phosphorus and nitrogen along agricultural open ditches to inform targeted and specific mitigation management - Opoku, D. G.; Healy, M. G.; Fenton, O.; Daly, K.; Condon, T.; Tuohy, P. (Frontiers in Environmental Science, 2024)
On dairy farms with poorly drained soils and high rainfall, open ditches receive nutrients from different sources along different pathways which are delivered to surface water. Recently, open ditches were ranked in terms of their hydrologic connectivity risk phosphorus (P) along the open ditch network. However, the connectivity risk for nitrogen (N) was not considered in that analysis, and remains a knowledge gap. In addition, the P connectivity classification system assumes all source-pathway interactions within open ditches are active, but this may not be the case for N. The objective of the current study, conducted across seven dairy farms, was to create an integrated connectivity risk ranking for P and N simultaneously, to better inform where and which potential mitigation management strategies could be considered. First, a conceptual figure of known N open ditch source-pathway connections, developed using both the literature and observations in the field, was used to identify water grab sampling locations on the farms. During field work, all open ditch networks were digitally mapped, divided into ditch sections, and classified in terms of the existing P connectivity classification system. The results showed that not all source-pathways were present across ditch categories for all species of N. This information was used to develop an improved open ditch connectivity classification system. Farmyard connected ditches were the riskiest for potential point source losses and outlet ditches had the highest connectivity risk among the other ditch categories associated with diffuse sources. Tailored mitigation options for P and N speciation were identified for these locations to intercept nutrients before reaching receiving waters. In ditches associated with diffuse sources, nitrate was introduced by subsurface sources (i.e., in-field drains and groundwater interactions from springs seepage and upwelling) and ammonium was introduced through surface connectivity pathways (i.e., runoff from internal roadways). On similar dairy farms where open ditches are prevalent, the integrated classification system and mapping procedure presented herein will enable a targeted and nutrient-specific mitigation plan to be developed. The same methodology may be applied to develop a bespoke integrated connectivity risk ranking for P and N along agricultural open ditches in other areas.